Halsbury's Laws of Malaysia: Islamic Law, 2016 Reissue, 14(2) - Shuaib, Farid Sufian; Mohd Kamal, Mohd Hisham; Ahmad Bustami, Tajul Aris; Hussin, Nasimah; Ramlee Saad, Zulfakar; Mohd Zin, Najibah; Abas, Afridah (LexisNexis, 2016)
This publication supersedes and replaces the existing Syariah Law title in Volume 14 (2006 Reissue). The volume discusses Islamic law, the constitutional position and the administration of Islamic law in Malaysia. It covers Islamic family law, Islamic criminal law, Syariah procedure, Islamic law of evidence and Syariah civil procedure. It provides perspective from fiqh, legislation and case law.